Manajemen Strategi Dalam Produksi Dokumenter Televisi “Titisan Nusantara” Edisi “ Jejak Warisan Budaya Sebatang Klembak Menyan” - Syakira, Luthfiah; Giantoro, Edi (Jurnal Jejak Hukum Indonesia (JHI), 2024)
Managing a production team in creating a television program requires a strategy to get the process and results according to plan. The thesis on the creation of the production work of Strategic Management in the Production of the Television Documentary "Titisan Nusantara" edition of "The Traces of the Cultural Heritage of Sebatang Klembak Menyan" aims to produce a production team management that has the strength to achieve the same vision and mission goals. The strategic aspect in managing the team is very important so that producers can use the Strength, Opportunities, Aspirations, Results (SOAR) analysis strategy in three stages of the production process, starting from pre-production, production, and post-production so that the production process runs comfortably for each element. In compiling this documentary program, two methods are used, namely observation and interviews with sources related to the work. This documentary work is presented with a historical documentary type. The producer uses several television programs as references to be developed into the "Titisan Nusantara" program edition of "The Traces of the Cultural Heritage of Sebatang Klembak Menyan". By using the SOAR analysis strategy, producers can focus on the strengths and interests of the team to achieve strategic thinking and planning in producing and leading a team to discuss the history of Klembak Menyan cigarettes optimally so that information can be conveyed to the public.